PENGARUH EDUKASI GIZI BERBASIS VIDEO TERHADAP PENINGKATAN PENGETAHUAN REMAJA PUTRI DI JAKARTA TIMUR (Jurnal Bakti Masyarakat Indonesia, 2021)
Compared to adolescent boys, adolescent girls have a higher risk of developing anemia. The need for iron absorption reaches its peak at the age of 14-15 years in adolescent girls. Anemia is a condition which the number of red blood cells is insufficient to meet the physiological needs of the body. The national prevalence of anemia in adolescent girls in Indonesia according to Riskesdas is 21.7%, this shows that anemia in adolescent girls is still a problem because the prevalence rate is still high. Anemia in adolescent girls can have adverse effects such as decreased reproductive health, motor and mental development, intelligence, learning achievement, fitness levels, and not achieving maximum height. Lack of knowledge can be a factor in the problem of anemia in adolescent girls. Several ways can be done to increase the knowledge and attitudes of adolescent girls, one of which is by providing nutrition education about balanced nutrition guidelines, clean and healthy living behavior, and knowledge about anemia with video-based as a tool. The purpose of the study was to determine the effect of video-based nutrition education on the level of knowledge of adolescent girls aged 15-21 years in the East Jakarta area.The level of knowledge was measured using a pre test before being given education and a post test after being given video-based education. The analysis used to process the data used statistical paired t-test. The results of the activity show that there is an effect of providing video-based nutrition education on the knowledge of adolescent girls aged 15-21 years in the East Jakarta area which is supported by a p-value